Comparing PROMIS computer adaptive tests to the Brief Symptom Inventory in patients with prostate cancer - Baum, George (Qual Life Res, 2014)
PURPOSE: This study assessed whether the Patient-Reported Outcomes Measurement Information System (PROMIS) computer adaptive tests (CATs) provided results similar to those of the Brief Symptom Inventory (BSI) with a low patient burden. METHODS: Secondary data analysis of 136 prostate cancer patients who completed the 53-item BSI and the PROMIS CATs assessing depression, anxiety, and hostility. RESULTS: The PROMIS CATs and BSI correlated significantly in measures of depression (.85), anxiety (.76), and anger/hostility (.66; p < .001 for all). Using our BSI cut-off points for depression, anxiety, and anger/hostility, ROC analysis yielded areas under the curve of .966 (standard error [SE] = .014, p < .001), .975 (SE = .012, p < .001), and .952 (SE = .027, p < .001), respectively. CONCLUSIONS: PROMIS CAT tests were highly correlated with the BSI subscales, indicating that the CATs performed well compared with the BSI, a widely used psychosocial measure.